Encounters in quest of Christian womanhood: the Basel Mission in pre- and early colonial Ghana - Sill, Ulrike (Studies in Christian mission, 2010)
The Basel Women's Mission in the European and the Basel context -- The women involved in Basel Mission encounters on the Gold Coast -- Embodying Christian womanhood : 'African' actors in the Basel Mission -- Christiansborg : acquiring space to propagate Basel femininity -- Akuapem and Akuropon (1) : establishing new spaces -- Akuapem (2) : existing loyalties and new options -- Innovation by women : the case of "six-fingered children" -- Creating a new female space : the Basel Mission girls' boarding schools -- Women's speech in the Basel Mission community and beyond